The Legacy of Nineteen Eighty-Four: British Dystopias, from 1984 to the present day - Claire Wrobel (Sillages Critiques)
This introductory piece looks back at the “Orwellian moment” that was the year 1984, which prompted a re-examination of Nineteen Eighty-Four’s potential prophecies and witnessed a dystopian resurgence in literature, then asks whether an Orwellian posterity can be traced in the British dystopias produced since then. After locating the dystopian genre on the utopian spectrum, in relation to terms such as “anti-utopia” or “metatopia”, it moves on to the reception of dystopia and to the question of hope. Can dystopias act as cautionary tales or do they just sell dissatisfaction as a commodity? The formal strategies to be found in contemporary dystopias are then examined. The latter’s preference for realism rather than science fiction, their focus on an individual protagonist, and the centrality of themes such as language, individual and collective memory and historiography may be regarded as evidence of an Orwellian posterity. However, new concerns have also emerged in the “post-totalitarian dystopia”, in which late capitalism is a predatory force that devours humans and nature. As such, British dystopias since 1984 display close links with genres such as post-apocalyptic fiction and climate fiction. Recent dystopias however never lose sight of the political, whether in the new forms state authoritarianism may take or in the deadly effects of fragmented plutocracies.